Music therapy and repetitive transcranial magnetic stimulation - nonpharmacological interventions in schizophrenia - Giba, Aleksandra; Niczyporuk, Patrycja; Zajkowska, Izabela; Iłendo, Kamila; Królikiewicz, Wiktor; Marecki, Rafał; Kicman, Aleksandra (Quality in Sport, 2025)
Objective: Music therapy (MT) has emerged as a promising non-pharmacological intervention for alleviating anxiety in cancer patients. However, the mechanisms underlying its effects remain unclear. This study aims to explore the influence of MT on the gut-brain axis, particularly its impact on gut microbiota, inflammatory cytokine regulation, and neurotransmitter levels. Materials and Methods: A literature review was conducted, analyzing studies on MT's effects on inflammation, gut microbiota composition, and neurochemical modulation in cancer patients and individuals with neuropsychiatric disorders, including schizophrenia and depression. Results: Research suggests that MT can reduce anxiety symptoms in cancer patients by lowering levels of pro-inflammatory cytokines such as IL-6 and IL-8 while modulating mood-related neurotransmitters like serotonin and dopamine. Additionally, studies indicate that MT may influence gut microbiota composition, which plays a crucial role in the gut-brain axis. Findings from schizophrenia studies further highlight MT’s potential in reducing psychotic symptoms, improving social interaction, and enhancing cognitive flexibility, though effects are often transient. Conclusions: MT presents a safe and effective method for improving emotional well-being and immune function in cancer patients. Its impact on the gut-brain axis suggests a novel therapeutic pathway, warranting further investigation. Additionally, MT's benefits for neuropsychiatric disorders reinforce its potential as an adjunctive therapy for broader clinical applications.